Serious Python : black-belt advice on deployment, scalability, testing, and more - Danjou, Julien (No Starch Press, Inc., 2019)
"Offers experienced coders advice and tips for improving knowledge of Python coding language. Includes interviews with Python experts and covers a wide range of common topics, from scaling and testing code to designing APIs"--